2007
DOI: 10.1167/iovs.06-1152
|View full text |Cite
|
Sign up to set email alerts
|

Topotecan Vitreous Levels after Periocular or Intravenous Delivery in Rabbits: An Alternative for Retinoblastoma Chemotherapy

Abstract: As a consequence of a favored passage across the blood-retinal barrier, considerable topotecan vitreous levels were detected in a rabbit model after systemic or periocular administration. Transscleral entry in vivo was constrained by rapid clearance from the administration site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 42 publications
1
49
0
Order By: Relevance
“…to investigate whether the retinal cancer stem-like cells display resistance to conventional chemotherapies, sphereforming cells and differentiated cells were exposed to carboplatin, a basic chemotherapeutic agent for retinoblastoma chemoreduction (1,30). Cell viable assays showed that sphereforming cells were dramatically resistant to carboplatin at different concentrations compared to differentiated cells (Fig.…”
Section: Sphere-forming Cells Display Chemoresistance To Carboplatinmentioning
confidence: 99%
“…to investigate whether the retinal cancer stem-like cells display resistance to conventional chemotherapies, sphereforming cells and differentiated cells were exposed to carboplatin, a basic chemotherapeutic agent for retinoblastoma chemoreduction (1,30). Cell viable assays showed that sphereforming cells were dramatically resistant to carboplatin at different concentrations compared to differentiated cells (Fig.…”
Section: Sphere-forming Cells Display Chemoresistance To Carboplatinmentioning
confidence: 99%
“…This conclusion was supported by untreated eye!s AUC ratio of vitreous/plasma was similar to previous systemic pharmacokinetic studies [60]. To confirm that the contralateral eye is exposed by the system an additional postmortem pharmacokinetic experiment could be carried out as Carcaboso and colleagues [152]. Rats could be sacrificed just prior to the subconjunctival injection and samples would we harvested a couple hours after administration [152].…”
Section: Pharmacokinetic Studiessupporting
confidence: 68%
“…To confirm that the contralateral eye is exposed by the system an additional postmortem pharmacokinetic experiment could be carried out as Carcaboso and colleagues [152]. Rats could be sacrificed just prior to the subconjunctival injection and samples would we harvested a couple hours after administration [152]. If the contralateral eye exposed by the systemic circulation, we would expect the postmortem untreated eye to be drug free.…”
Section: Pharmacokinetic Studiesmentioning
confidence: 99%
“…As published previously [15][16][17][18] , topotecan can traverse the blood-retinal barrier into the vitreous humor or into the systemic circulation. In the present study, 2 μg of topotecan reached sufficient concentrations in plasma and in the contralateral vitreous humor.…”
Section: Discussionmentioning
confidence: 71%
“…Topotecan, a specific topoisomerase I inhibitor that is capable of producing lethal damage during the course of DNA replication 11,12 , has shown promising antitumor activity in pediatric solid tumors and leukemia [13][14][15] . The first study to examine the pharmacological penetration of topotecan into the vitreous cavity in animals demonstrated that periocular delivery of topotecan reached potentially active levels in the vitreous humor but sys- temic absorption accounted for most topotecan delivery 16 . Rapid drop-off in vitreous concentration of chemotherapeutic agent after periocular delivery is an impediment to efficacy.…”
Section: Introductionmentioning
confidence: 99%